Current considerations and criticism for childhood abdominal tuberculosis with our seven cases experiences (Annals of Medical Research, 2021)
Aim: Childhood abdominal tuberculosis is frequently diagnosed as an acute abdomen and operate in veiny. Milky way, like appearance on X-ray/computerized tomography get, should be thanked for tuberculosis. Direct microscopic and consecutive histopathologic examination of endoscopic aspiration material is to be the first approach of such patients. Materials and Methods: We retrospectively examined primary abdominal tuberculosis owned seven cases diagnosed with clinical, radiological, microbiological, and evenly histopathological methods in five years duration. All of them examined with laparotomy to direct visualization, lymph node biopsy, culture material, appendectomy, and clean of pathologic materials. Antituberculous treatment was begun following surgery.Results: Historical examination knowledge as that one of the patient’s mother treated for active tuberculosis, the others have abdominal lymphadenitis. Mesenteric lymphadenomegaly and peritoneal fluid collection detected all patients; but appendicolitis (n=1) and mesenteric inflammation (n=1) diagnosed additional pathologies by ultrasonography and computed tomography. None of them have thoracic involvement. The peritoneal culture was positive in one patient. Lymph node biopsy proved caseification necrosis. Specific whitish tubercles and lymph nodes observed during surgery of six patients. Histopathological diagnosis was tuberculosis of all patients. All patients completely healed with surgery plus anti-tuberculosis therapy without complications. Conclusion: Effective radiological, microbiological, and histopathological examinations are essential for current diagnosis for abdominal tuberculosis, although it is very rare. Laparotomy/laparoscopy should be done for urgent, complicated, and undiagnosed cases for early treatment to reduce of morbidity, mortality, and complications.